TACTILE CARTOGRAPHY EXPERIENCES IN BRAZIL: METHODOLOGIES AND DIDACTICAL MATERIAL WITH TECHNOLOGICAL RESOURCES FOR INCLUSION OF BLIND AND LOW VISION STUDENTS - Castreghini de Freitas, Maria Isabel [UNESP] (Iated-int Assoc Technology Education A& Development, 2012)
The tactile cartography is an area of Cartography that aims the development of methodologies and didactical material to work cartographic concepts with blind and low vision people. The main aim of this article is to present the experience of Tactile Cartography Research Group from Sao Paulo State University (UNESP), including some didactical material and courses for teachers using the System MAPAVOX. The System MAPAVOX is software developed by our research group in a partnership with Federal University of Rio de Janeiro (UFRJ) that integrates maps and models with a voice synthesizer, sound emission, texts, images and video visualizing for computers. Our research methodology is based in authors that have in the students the centre of didactical activity such as Ochaita and Espinosa in [1], which developed studies related to blind children's literacy. According to Almeida the child's drawing is, thus, a system of representation. It isn't a copy of objects, but interpretation of that which is real, done by the child in graphic language[2]. In the proposed activities with blind and low vision students they are prepared to interpret reality and represent it by adopting concepts of graphic language learned. To start the cartographic initialization it is necessary to use personal and quotidian references, for example the classroom tactile model or map, to include concepts in generalization and scale concerning to their space of life. During these years many case studies were developed with blind and low vision students from Special School for Hearing Impaired and Visually Impaired in Araras and Rio Claro, Sao Paulo - Brazil. The most part of these experiences and others from Brazil and Chile are presented in [3]. Tactile material and MAPAVOX facilities are analysed by students and teachers who contribute with suggestions to reformulate and adapt them to their sensibility and necessity. Since 2005 we offer courses in Tactile Cartography to prepare teachers from elementary school in the manipulation of didactical material and attending students with special educational needs in regular classroom. There were 6 classroom and blended courses offered for 184 teachers from public schools in this region of the Sao Paulo state. As conclusion we can observe that methodological procedures centred in the blind and low vision students are successful in their spatial orientation if use didactical material from places or objects with which they have significant experience. During the applying of courses for teachers we could see that interdisciplinary groups can find creative cartographic alternatives more easily. We observed too that the best results in methodological procedures were those who provided concreteness to abstract concepts using daily experiences.
Keywords: Tactile cartography; didactical material; MAPAVOX; inclusion; blind students; technological resources